Retrospective Study of Oral and Maxillofacial Trauma in Portuguese Population - Cristiana Maria Palmela Pereira; Adriana Resende dos Santos; Catarina Rodrigues Gonçalves; Valon Nushi; Francisco Coutinho; Francisco João Salvado e Silva; Rui Filipe Vargas de Sousa Santos (University of Zagreb. School of Dental Medicine, 2023)
Objective: The increasing significance of medicolegal evaluation following maxillofacial traumatic events constitutes a complex issue. This clinical research aimed to assess the current etiology of oral and maxillofacial injuries in Portuguese population. Material and methods: An epidemiological clinical observational study was conducted in Centro Hospitalar Lisboa Norte on a sample of 384 subjects diagnosed with oral and maxillofacial trauma, between 2018 and 2020. Data were collected through clinical reports and analyzed using SPSS version 27. Results: Women and men were nearly identical in the number and distribution, with 49.5% females and 50.5% males. In 2020, there was a decrease in the number of traumatic incidents compared to other years. Falls or accidental descents were found to be the most common cause of injury, accounting for 44.3%, followed by assaults accounting for 24.7%. A total of 84 subjects exhibited soft tissue injuries related to periodontal region. The upper central incisors (174) were the most frequently affected teeth with uncomplicated fractures, and the predominant form of treatment was the administration of pain medication. Conclusion: A correlation between falls or accidental descents, female subjects, and advancing age, as well as between assaults, male subjects, and adults, has been established. Falls or accidental descents and assault were the predominant etiologies, and the year 2020 exhibited a decrease in the incidents of traumatic events.